Financial inclusion through WhatsApp banking in Johannesburg - Miller, Jade Rowan (University of the Witwatersrand, Johannesburg, 2022)
Approximately three billion people will use mobile banking by 2024. Mobile devices and widespread Internet access are helping to boost mobile banking's popularity. Retail banks can now offer their customers even more convenience with mobile banking applications like WhatsApp. Consumers and financial institutions have embraced advanced technologies, including mobile banking, in recent years. Social media, mobile banking and new ideas like WhatsApp banking have made it easier for people to do business. Mobile banking is now possible thanks to high smartphone penetration and technological advancements. The fourth industrial revolution will continue to exponentially transform the modern economy. Globalisation has forced banks to open new channels to remain competitive in today's market. Banks have had to cut costs and improve their financial position by introducing new products and services. Mobile banking has grown rapidly globally due to the rapid development of information technology. Due to multi-channel distribution, most banks now have a global presence with cross-border customers. A quantitative approach was taken to examine factors that may influence behavioural intention to use WhatsApp banking in the context of financial inclusion. A questionnaire was used as the primary data collection instrument. The survey was conducted using an online questionnaire distributed to people living in Johannesburg, South Africa. The study adds to the body of knowledge by identifying factors that influence WhatsApp banking adoption, particularly in developing countries. The Technology Acceptance Model by Davis (1985) was used to investigate behavioural intention to use WhatsApp banking. My findings show that perceived trust, banking inclusion, perceived usefulness and awareness all play a significant role in WhatsApp banking adoption. Managers in financial institutions should focus on increasing consumer trust across all age groups to increase customer comfort with non-traditional banking platforms in general and thus increase financial inclusion. This is crucial because ix WhatsApp banking has the potential to bank the unbanked and underbanked while also increasing financial inclusion.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Africa; South Africa; Financial Inclusion; Banking; Technology Acceptance Model (TAM); WhatsApp Banking; Unbanked; Underbanked; UCTD; SDG-8: Decent work and economic growth